SUSTAINABLE DEVELOPMENT PLANNING – THE CASE OF MACEDONIA - KJosev, Sasho; Eftimov, Lјupcho (MESTE NGO, 2015)
To meet the challenges of sustainable development, strategic planning practices need to become more effective, efficient, credible and lasting. A sustainable development strategy is a tool for informed decision-making that provides a framework for systematic thought across sectors and territory. Following the recommendations of the UN World Summit on Sustainable Development in Johannesburg 2002, Macedonia developed a national strategy for sustainable development, for the period 2009-2030. The proposal for the overall strategy comprises of two main parts: (1) long-term, intermediate and short-term objectives, which timely address the important issue of EU accession as well as making the Republic of Macedonia sustainable, and (2) seven strategic thrusts, which address what to focus on in order to make the Republic of Macedonia sustainable. However, what is still missing is complex methodological and analytical framework for sustainable development analysis (Social Accounting Matrix, SESAME approach, NAMEA approach). Hence, one should point to the fact that sustainable development and sustainable development planning are complementary processes which should ultimately lead to increased well-being of the mankind.
Keywords: planning, sustainable development, strategy, methodology, Macedonia